The Effect of Resilience and Quality of Work Life on Work Engagement for Employees Working in the Era of the Covid-19 Pandemic - Kamila Sagafia; Winny Puspasari Thamrin (Journal of Social Research, 2022)
Background: Resilience can be defined as the capacity to bounce back from adversity and become smarter and stronger. Saying that resilience is an active process of resilience, self-improvement, and self-growth in response to crises and challenges. Objective: aims to empirically examine the effect of resilience and quality of work life on work engagement for employees who work in the era of the covid-19 pandemic. Methods: using a purposive sampling technique with the samples used are male and female employees who work in the era of the covid-19 pandemic with characteristics aged 23 to 57 years, in companies that apply work from home and work from office. Results: The hypothesis test that has been carried out has a significance of 0.000 (p < 0.05), which shows that there is a significant effect between resilience and quality of work life on work engagement for employees who work in the era of the covid-19 pandemic. Conslusion: Based on the results of the analysis that has been carried out in this study, it is known that all the hypotheses proposed in this study can be accepted. So it can be concluded that there is a significant effect of resilience on work engagement because it has a significance value of 0.000 (<0.05), there is a significant influence between quality of work life on work engagement because it has a significance value of 0.000 (<0.01), and there is a significant effect on work engagement. significant relationship between resilience and quality of work life    on    work    engagement    because    it    has    a significance         value        of        0.000        (<0.01).